Determinants of Postnatal Care Service Utilization Among Mothers in Bangladesh: A Two‐Level Binary Logistic Regression Approach - Md. Obaydul Hossain; Susmita Rani Dey; Uttam Kumar Majumder (Health Science Reports, 2026)
ABSTRACT Background and Aims Postnatal care is essential for mothers and their children to address any future problems and provide the mothers crucial health information. Most maternal and newborn deaths occur during postnatal period. Maternal mortality can be significantly reduced by increasing the utilization of postnatal care service. This study aimed to identify the prevalence and factors associated with postnatal care (PNC) service utilization among mothers in Bangladesh. Methods This study utilized the latest data from the Bangladesh Demographic and Health Survey 2022. A total of 4899 mothers were included for the analysis. Two level binary logistic regression was used to identify associated factors with PNC utilization. Results Around 61.6% of mothers utilized PNC service from a medically trained provider within 42 days after delivery. The prevalence was higher among women in Khulna division (79.1%) and lowest was (48.9%) in Sylhet division. In this study, among individual level variables, respondent education, wealth index, place of delivery, mode of delivery and Antenatal care (ANC) visits were significantly associated with PNC utilization. At the community level, community ANC visits and division had a significant association on the utilization of PNC services. Among the significant individual‐level factors, it was found that the place of delivery and the mode of delivery exhibited considerable randomness across different communities. Conclusion PNC utilization was significantly associated both individual‐ and community‐level variables. Targeted strategies should be developed to improve PNC utilization, especially in administrative divisions with lower education levels. It is crucial to ensure that women receive at least eight antenatal care visits, and those delivering at home should be strongly encouraged to seek PNC service to improve maternal and child health outcomes.